Lecto-escritura en el proceso de enseñanza-aprendizaje en estudiantes de cuarto grado de educación general básica en la escuela mixta Dr Rodrigo Ugarte Cordova Pasaje 2014-2015 - Macas Armijos, Andrea Verónica (2015)
A proposal Intervention planted with propósito improve academic process of students, this educational workshop is aimed at teachers and teachers with the m order to awaken and promote interest in the process of reading and writing which expose a series of interactive and innovative activities that facilitate Academician of studying process, also provide guidance and assistance documented INFORMATION teachers a flap that what prevails in practical, achieving de este so that students develop skills and Skills seeking a Quality Education and excellence, forming Individuals Integrales for good living.